?WHEAT (TRITICUM AESTIVUM L.) STAND ESTABLISHMENT IN LEGUME AND NON-LEGUME BASED CROPPING SYSTEMS - Aslam, Muhammad; Hashmi, N I; Majid, A; Ahmad, Iftikhar; Razzaq, A (Biological Sciences - PJSIR, 1998)
Wheat stand establishment behaviour was studied in different cropping systems under rainfed conditions, during 1992- 94. On the basis of wheat emergence (rn") and emergence rate index, two distinct groups of cropping systems were observed. The first group included fallow-wheat, mashbean-wheat, mungbean-wheat and cowpea-wheat systems whereas the second included maize-wheat, sorghum-wheat, millet-wheat, sunflower wheat and soy bean-wheat systems. Wheat stand establishment was significantly (P<0.05) higher in the first group than in the second group. In Rabi 1992-93 wheat emergence was completed in a short period and emergence rate index was higher than that for 1993-94 due to dry weather. Overall, there was significantly (P<0.05) better residual soil moisture (0-15 em layer) in fallow-wheat, mashbean-wheat, mungbean-wheat and cowpea-wheat cropping systems than other systems under study during both the years.